The Impact of Online Games on the Academic Performance of Second-Year English Major Students at Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Technology has been part of our lives and is continuously evolving. It comes with different platforms that are believed to be helping us in making our lives convenient and easy. The fact that we live with Technology opens the door to opportunities where everyone can explore and innovate.  One of the widely used platforms brought by technology is the internet. This provides information that plays a vital role in developing our skills and experiences in life. This can be considered the most effective way of learning and coping with the challenges brought by the pandemic. Everybody believes that technology has made life easier and more convenient, leading to being more inclined with it, where it has become a necessity already regardless of age or sex today. However, this influence is not always seen as an advantage, and there has been undeniable proof that it causes problems, especially for the youth. These technologies are very good at distracting people. In line with this, online games were made to give people entertainment.  Online gaming is a widely used leisure platform by many. They believed that this would help them cope with stress, and for some, this boost their confidence as there are online games that deal with competition and challenge, but the exaggerated part is that they feel like this will help them mentally escape their real problems. Undeniably, online games have opened a world of illusion where they can escape, especially for teenagers. For most adolescents, gaming is a pleasurable pastime. At school, they feel burned out with loads of work; this is how they cope and relieve themselves. These students are seen to be more active and strategic as they apply their tactics from online games to the real world.  However, these reasons are quite overrated and are associated with the problems of lack of discipline and poor time management that result in poor academic performance. Furthermore, some issues relating to their behaviour have occurred, particularly in dealing with “real people.” Hence, the researchers felt the need to particularly determine the impact of online games on the academic performance of the 2nd year English major students at BESTLINK COLLEGE OF THE PHILIPPINES.   This study employs a qualitative - non-experimental design utilizing descriptive survey methods to investigate information regarding the impact of online games on the academic performance of second-year English major students at BESTLINK COLLEGE OF THE PHILIPPINES. Simple Random Techniques were used to select 30 second-year students at BESTLINK COLLEGE OF THE PHILIPPINES. Data were collected via a survey questionnaire. The data were analyzed quantitatively and were using tables and graphs. Online games, especially for English major students, can affect students' behaviour and attitude. Among the items on the questionnaires, the "social anxiety" and "get easily irritated" in behaviour got the same highest rank with an overall weighted mean of 3.2. While "bullying" got the lowest weighted mean of 2.1 for behaviour. In Academic performance, "lack of focus" has the highest weighted mean of 3.6, while "absenteeism" has the lowest weighted mean of 2.5. As for skills, the data imply that online games have the highest impact on the students' skills, with an overall weighted mean of 3.7. Therefore, we must guide them in choosing what they play to at least lessen the negative effects of online games. The results are taken from the data gathered. The majority of the gender respondents are females, 66.7%, and their ages are 17-20, a percentage of 63.3% and an income of 5,000 and below with a percentage of 50%. Among the online games, mobile legends are the most used by the respondents, with a percentage of 80%. Most of the students spent 1-2 hours and below. The researchers discovered the impact of online games on the academic performance of second-year English major students at BESTLINK COLLEGE OF THE PHILIPPINES as to behaviour, academic performance, and skills, especially the "item social anxiety” and "get easily irritated" that the same highest rank the weighted mean of 3.2. and "absenteeism" got the lowest weighted mean of 2.5. Also, we found out the biggest problem encountered by the respondents was attendance, and the use of jargon/slang words placed the least.